The Implication of the Development of Technology on Land Transportation Law in Indonesia - Sidiqah, Meliyani (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The emergence of online transportation provides significant changes in various aspects of people's lives. But its success raises protests from several groups for the abolition of online transportation. The rapid technological development of land transportation that cannot be accommodated by Indonesian law can affect the certainty of law. Further, it can provide legal protection to related parties.Purposes of the Research: This research aims to analyse the implication of online transportation as land transportation in Indonesia, and to recommend the accommodation of online transportation in Law Number 22 of 2009 on Road Traffic and Transportation to the Government of Indonesia.Methods of the Research: This research employed the normative juridical method by examining secondary data collected from library research using the statutory approach method analysed by qualitative technique.Results of the Research: The results show that the existence of online transportation as land transportation has positive implications for society such as the easier process, saving time, saves energy, can identify drivers, can track routes and vehicle locations, traffic monitoring, safety standards, lower costs, promos and discounts, efficient payment methods, and driver services. The other benefits are reducing the unemployment rate, increasing people's income, reducing the number of poverties, improving the people's welfare, and increasing the productivity of every institution and company. So, the government of Indonesia must accommodate online transportation in Law Number 22 of 2009 on Road Traffic and Transportation.